2021
DOI: 10.1108/jhti-01-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

WTPP for ecotourism: the impact of intention, perceived value, and materialism

Abstract: PurposeThis study examines the impact of perceived value, materialism and tourist intention on willingness to pay a premium for ecotourism (WTPP).Design/methodology/approachData were collected and conducted in Vietnamese National Parks. The dataset consists of 927 valid responses by domestic travelers. Structural equation modeling (SEM) was used to test the proposed relationships among perceived value, materialism, tourist intention and tourists' WTPP.FindingsThis study found a significant positive effect of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…The commitment to sustainability and ecology can be a differentiating element that can be transformed into a unique selling proposition. Furthermore, ecotourists are willing to pay more (Hultman, Kazeminia and Ghasemi, 2015;Kazeminia, Hultman and Mostaghel, 2016;Duong, et. al., 2021) for an eco-touristic product.…”
Section: Source: Own Elaboration Based On the Resultsmentioning
confidence: 99%
“…The commitment to sustainability and ecology can be a differentiating element that can be transformed into a unique selling proposition. Furthermore, ecotourists are willing to pay more (Hultman, Kazeminia and Ghasemi, 2015;Kazeminia, Hultman and Mostaghel, 2016;Duong, et. al., 2021) for an eco-touristic product.…”
Section: Source: Own Elaboration Based On the Resultsmentioning
confidence: 99%
“…Consumers may be willing to pay up to 10% more at restaurants which they perceive as positively incorporating sustainable practices (Parsa et al, 2015). Likewise, Duong et al (2022) found that the perceived value of ecotourism positively influences tourists' WTPP. In conclusion, consumers' WTPP for sustainable products is determined by their overall assessment of the benefits they received.…”
Section: The Effect Of Perceived Value On Willingness To Pay Premiummentioning
confidence: 99%
“…Ecotourism development has got widespread attention from both academic researchers and industry practitioners (KC et al , 2021; Kalyar et al , 2021; Molina-Collado et al , 2022; Pablo-Cea et al , 2021; Vyasha et al , 2021). Studies have also examined ecotourism knowledge of the tourists to check their travel activities in particular (Duong et al , 2021; Khanh, 2020; Li et al , 2021; Oviedo-García et al , 2019). However, to make the policy successful, it is equally important to understand the influence of the impact of ecotourism on residents' behavior.…”
Section: Review Of Literaturementioning
confidence: 99%